UNDERSTANDING OVER-EDITING BEHAVIOR OF INDONESIAN TRANSLATORS: A COGNITIVE READINESS APPROACH - Ryan Hilman Aziz; Esti Junining; Sri Endah Tabiati (IKIP Siliwangi, 2023)
Due to the excessive usage of the assisted-translation machine, abundant translators create defective translation documents. This phenomenon expands to the ignorance of translators’ foundational abilities, such as mastering metalinguistic skills and vocabulary expansion. Thus, this study investigates to what extent translators rely on assisted-translation machines to translate rather than preparing their cognitive and psychological maturity, culminating in over-editing behavior. It uses a survey method to collect data from an Indonesian translator’s community, namely “Himpunan Penerjemah Indonesia” (HPI), reflecting the translators’ over-editing behavior in translating documents from their clients. Before distributing the questionnaire, the authors employed a pilot test, achieving high feasibility. Firstly, it found that cognitive readiness plays a significant role in translation processes because, in either translation agencies or self-employment, translators must master specific language knowledge for both source- and target language. Secondly, both full- and full-member translators revealed different perspectives on translating readiness, indicating mental maturity differences due to lack of experience, different mindsets, and broad knowledge capacities and capabilities, leading to dissimilar behavior in utilizing technology. Finally, this study commemorates that thorough consideration before using technology is necessary, contemplating its benefits and drawbacks and positing translators’ skills and knowledge as a fundamental translation process, diminishing over-editing behavior. Keywords: Translators; Over-Editing; Operational Cognitive Readiness; Mental Preparation